The Discourse of Infatuation in John Keats’s Letters and Poems to Fanny Brawne (American & British Studies Annual, 2012)
Seen from the vantage point of the Victorian sensibility, John Keats’s letters to Fanny Brawne transgress the norms of respectability,  being too personal, too passionate and too direct.  Moreover, they define Keats as a sensuous, therefore effeminate poet who allows himself to be flooded by emotions and passion. After the publication of the letters in 1878, the perception of Keats as “feminine” became standard during the Victorian era. This paper proposes to look at chosen letters and poems which Keats wrote to Fanny Brawne in order to see how the problematic discourse of infatuation can account for the charges of effeminacy brought against the poet. Strikingly, although Keats expresses love and devotion in his letters and love poetry, at the same time he articulates much more ambivalent attitudes to femininity in general. Therefore, it can be suggested that the problematic relations between male and female characters in Keats’s verse (where the woman is frequently figured as either the threatening femme fatale or the indifferent muse) can be better understood in the context of his conflicted views on gender matters. Finally, my interpretation facilitates the understanding of the “camelion Poet” concept, one of the chief ideas concerning Keats’s poetic theory.
Keywords: John Keats; Fanny Brawne; women; letters; infatuation; fear